Serum levels of sCD36 and cardiometabolic variables in two Peruvian towns: Carhuamayo (4100 masl) and Mala (30 masl) - Carranza Alva, Elizabeth (2017)
Objectives: To determine the serum levels of sCD36, a lipid metabolism-related molecule, in high-altitude and sea-level populations, and to establish the association of this parameter with cardiometabolic risk factors. Materials and methods: The study population consisted of 45 people from Carhuamayo (4100 masl) and 40 people from Mala (30 masl). Weight, height and blood pressure were measured. Hemoglobin was determined in whole blood, and glucose, lipid profile and sCD36 in serum. Results: It has been found that hemoglobin levels in the population of Carhuamayo were significantly higher, while weight, BMI and glucose level were significantly lower than those in the population of Mala. There was no significant difference between serum levels of sCD36 in both populations. A significant difference was observed between sCD36 mean serum levels of both populations based on the BMI, and a significant positive correlation between sCD36 and the weight and BMI. Conclusions: The observed sCD36 serum level is not related to the altitude and can be considered as a potential marker of metabolic syndrome.